A survey of the experiences of families with bereavement support services following a perinatal loss. (28th June 2017) - Inati, Violet; Matic, Mara; Phillips, Christine; Maconachie, Nathalie; Vanderhook, Fiona; Kent, Alison L.
Abstract : Background: Although there are many studies that explore complicated grief, no studies have examined the impact of bereavement support services on the progression to complicated grief. The aims of our study were to describe the types of bereavement services utilised by families who have experienced a perinatal loss, and explore the impact of these services on the families' bereavement journey. Methods: Women who experienced a perinatal loss were sent a survey consisting of the modified Perinatal Post Traumatic Stress Disorder (PTSD) questionnaire, items addressing use of bereavement services, and the Inventory of Complicated Grief. Respondents also provided free‐text comments. Results: Forty‐seven women were included in the study (34% response rate); 75% had a perinatal PTSD score which indicated the need for support from mental health services and 75% accessed services. Forty‐three percent met the criteria for complicated grief. Women whose PTSD scores were in the highest quartile were most likely to access services; 45% of surveyed women used SIDS and Kids of the Australian Capital Territory (SKACT) accessing counselling (90%), support groups (50%), playgroups (15%) and the helpline (10%). Fifty‐seven percent of women surveyed accessed non‐SKACT services and predominantly used psychologists (66%) and general practitioners (30%). Requests were made for grief training of hospital staff, and for referral to bereavement services to be offered after hospital discharge. Conclusions: Following a perinatal loss, a high proportion of women had high PTSD scores and complicated grief despite utilising local bereavement services. Our findings support the continuation of current support services with modifications that may potentially improve recovery following a perinatal loss.